LOCAL WISDOM TRACES IN BASIC EDUCATION LEARNING - Laelia Nurpratiwiningsih; Rusdarti Rusdarti; Joko Widodo; Tjaturahono Budi Sanjoto (Program Studi PGSD Universitas Flores, 2026)
Social Studies (IPS) education plays a crucial role in understanding local wisdom as a cultural resource that supports sustainable development and is responsive to social contexts. This study explores the integration of local wisdom into elementary school curricula and learning practices using ethnographic qualitative methods, including in-depth interviews with teachers, classroom observations, and document analysis. The results indicate that local wisdom is embedded in local languages and dialects, in folklore, and in arts and crafts. However, challenges such as a lack of teacher training and limited resources were also identified. This study emphasizes the importance of well-planned pedagogical strategies to develop students' character and social attitudes.